Impuesto selectivo al consumo en el mercado de combustibles y su relación con el crecimiento económico de Loreto periodos 2007 - 2019 - Filomeno Torres, José Alejandro (2022)
The purpose of the study was to estimate the relationship, through correlation coefficients, between the selective tax on fuel consumption and the economic growth of the Loreto region, during the period 2007 and 2019. For this, quantitative analyzes were carried out, using statistics descriptive and through inferential statistics, through two statistical models to calculate, evaluate and analyze the correlation coefficients of the variables, these were the Pearson correlation model and the Spearman correlation model. Our results show that investment is positively correlated with economic growth and that this correlation is good with a correlation coefficient of 0.63, the variable Public Expenditure is also positively correlated with economic growth and is a good correlation, even higher to the correlation of investment and economic growth, with a correlation coefficient of 0.76, but the selective consumption tax has a positive but low correlation with economic growth, which is 0.065, unemployment has a negative correlation with growth economy of Loreto. Given our results, we can validate both our general and specific hypotheses, since we demonstrate quantitatively that the selective consumption tax has a direct relationship with economic growth, and public spending, tax collection and investment have a positive relationship with economic growth. in Peru, during the period 2007 - 2019.